Antigen distribution frequency of Han and Tujia polyhemia systems in Chongqing - YIN Pengwei; LIU Bujin; CUI Danli; DAI Huayou; ZOU Haiman; WU Siqi; HUANG Xia; XU Yongzhu (Zhongguo shuxue zazhi)
[Objective] To analyse the distribution of antigen phenotypes in the Rh, MNS and Kidd blood group systems of Han and Tujia blood donors in Chongqing, and to provide data support for the establishment of an expanded blood group antigen phenotype database and the development of expanded blood group coordinated transfusion in blood donors. [Methods] The antigens of Rh, MNS and Kidd blood group systems in Han and Tujia blood donors in Chongqing were detected by test-tube method, and the Hardy-Weinborg anastomosis of the three blood group systems was calculated. Pearson's chi-square test and Fisher's exact probability method were used to compare the differences in phenotypic distribution frequencies among different regions and ethnic groups. [Results] Han and Tujia blood donors accounted for the highest proportion of CCee in the antigenic phenotype of the Rh blood group system, followed by CcEe, and then Ccee and ccEE. Tujia blood donors accounted for 52.02% of CCee, which was higher than that of Han blood donors (47.24%), while Han blood donors accounted for 32.20% of CcEe, which was higher than that of Tujia blood donors (28.94%). In the antigenic phenotype of the MNS blood group system, the blood donors of Han nationality and Tujia were MN>MM>NN,. The antigen phenotype distribution frequency of the Kidd blood group system was highest for Jk(a+b+) among both Han and Tujia blood donors, and the blood donors of Han nationality were Jk(a+b+)>Jk(a+b+), while those of Tujia were Jk(a-b+)>Jk(a+b-). The antigens of the three blood groups of Han and Tujia blood donors were consistent with the Hardy-Weinberg balance(P>0.05). There was no statistically significant difference in the frequency of antigen phenotypes of the three blood group systems between Han and Tujia blood donors(P>0.05). There were statistically significant differences in the phenotypic distribution frequency of Rh antigens between Chongqing and Xi'an, Zhejiang, Shantou, Foshan, Nanning and Yangzhou(P<0.05), but not with Guang'an and Shenzhen(P>0.05). There were statistically significant differences in the phenotypic distribution frequency of Rh antigens between Han, Tujia, Zang, Mongolian, Korean and Hani ethnic groups in Chongqing(P<0.05). There were statistically significant differences in the phenotypic distribution frequency of MNS antigens between Han blood donors in Chongqing and Urumqi, Hainan and Yuncheng, but not with Xi'an and Wenzhou. There was a statistically significant difference in the phenotypic distribution frequency of MNS antigen between Tujia blood donors in Chongqing and Urumqi and Hainan(P<0.05), but there was no significant difference in the phenotypic distribution frequency of MNS antigen between Tujia blood donors in Chongqing, Urumqi and Hainan(P>0.05). There was a statistically significant difference in the phenotypic distribution frequency of Kidd antigens between blood donors in Chongqing and Harbin(P<0.05), but not in Huizhou, Wenzhou and Yichang(P>0.05). [Conclusion] The population in Chongqing has multi-ethnic characteristics, and the antigenic phenotypes of Rh, MNS and Kidd blood group systems exhibit diversity and regional differences. Establishing an expanded blood bank can provide more options for precision blood transfusion.